2022
DOI: 10.1155/2022/6392172
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Green Marketing on Brand Trust: The Mediation Role of Brand Image and the Moderation Effect of Greenwash

Abstract: For the purpose of understanding the effect of green marketing on brand image, this paper has added mediation variable namely brand image into the research model; meanwhile, in order to better discuss about this issue in the context of green marketing, the paper considers that greenwash is an indispensable element in adjusting green marketing’s effect on the brand. The paper has used the method of a questionnaire survey to distribute questionnaires on online social platforms. A total of 500 questionnaires have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 34 publications
1
10
0
3
Order By: Relevance
“…BT can increase client loyalty and favour positive word-of-mouth (PWOM), and this in turn builds up BL. These assertions are in line with the results of prior studies which emphasised the key role of BT in building BL (e.g., Munaier et al, 2022;Tan et al, 2022;Li et al, 2022;Haudi et al, 2022;Wu & Liu, 2022;Adha & Utami, 2021;Khadim et al, 2018).…”
Section: Dr Maha Misbah Shabanasupporting
confidence: 89%
See 2 more Smart Citations
“…BT can increase client loyalty and favour positive word-of-mouth (PWOM), and this in turn builds up BL. These assertions are in line with the results of prior studies which emphasised the key role of BT in building BL (e.g., Munaier et al, 2022;Tan et al, 2022;Li et al, 2022;Haudi et al, 2022;Wu & Liu, 2022;Adha & Utami, 2021;Khadim et al, 2018).…”
Section: Dr Maha Misbah Shabanasupporting
confidence: 89%
“…Bhattacharya, 2006;Tao & Ji, 2020;Hafez, 2015;Lagasio et al, 2021;Dawood, 2019). In addition, other studies revealed that BT has a positive effect on BL (e.g., Wu & Liu, 2022;Haudi et al, 2022;Tan et al, 2022;Benson, 2022;Adha & Utami, 2021;Zehir et al, 2011). Accordingly, when customers trust in a certain brand especially in situation of uncertainty like the COVIID-19 pandemic, they will be more loyal for that brand.…”
Section: 3the Moderating Role Of Brand Trustmentioning
confidence: 98%
See 1 more Smart Citation
“…In this era, consumer's knowledge of pollution control, strict governance, and demand for green buying is increasing substantially (Poltarykhin et al, 2018; Wu & Liu, 2022). Now consumers are more sensitive about the social and ethical considerations of businesses towards society and expect the whole business operations to be in favor of society and the environment.…”
Section: Introductionmentioning
confidence: 99%
“…Greenwashing refers to the poor performance of an organization that deliberately disguise the facts that the company is polluting the environment to build a good environmental image [6]. Ample empirical evidence shows that greenwashing behavior has a persistent negative impact on organizations and their customers [7][8][9][10][11][12][13]. In order to better understand how greenwashing can have negative consequences for companies, research on the consequences of greenwashing is gradually increasing.…”
Section: Introductionmentioning
confidence: 99%